M&AXCELLENCE - Handling The Cultural And Psychological Complexity Of International M&A`s As Organizational Capability - Miller, Moritz (Digital Repository of Theses, 2026)
The aim of this research is the development of an applicable, people-centric M&A excellence framework that addresses the complexity of culture and psychology in international company transactions. For decades, M&As have been supporting the growth and expansion strategies of organizations across all industries. However, reported high failure rates emphasize that achieving the initial M&A objectives is challenging, and many reasons for failure are related to the importance of human factors, such as cultural clashes or psychological reasons like resistance, fears, or distrust, which are even more critical in an international environment. Although the individual challenges have been examined and the literature on M&A and culture is vast, organizations are not sufficiently able to benefit from this knowledge through implementation, and a lack of comprehensive approaches was identified. Therefore, this work aims to answer the following research question: How can organizations be enabled to holistically address the cultural and psychological complexity of international M&As as organizational capability and driverfor M&A excellence? With a focus on the applicability of all developments, the literature was systematically and critically reviewed to create a solid knowledge basis regarding culture, psychology, change, M&A, and ways to enable organizations to develop capabilities and excellence. This was followed by an extensive primary data collection through a multiple case study approach with 100 interviews, covering 17 M&A cases within the predominantly examined organization, reflected against external expertise and experiences. Synthesizing the findings from secondary and primary data led to the creation of M&AXCELLENCE®, a comprehensive framework which provides tools to understand and discuss relevant dimensions of culture and psychology, and reasons for M&A failure and success, to analyze national and organizational culture as basis for conscious integration decisions, and to enable leaders to focus on individual needs of employees, especially in critical phases of transformation. These practical approaches are embedded in a systematic model which compiles necessary measures regarding strategy, roles, processes, and knowledge for organizational excellence, M&A competences, and intercultural capabilities. This framework was critically appraised and verified by two focus groups. It facilitates organizational learning and continuous improvement with emphasis on human factors, and can contribute to sustainable success by bridging the identified gap between theory and practice.